Mempercepat Waktu Pelaksanaan Proyek Pembangunan Jalur Ganda Kereta Api Antara Mojokerto-Sepanjang Melalui Penjadwalan Line of Balance - Cristina Widya Ningrum; Michella Beatrix (Faculty of Engineering, Kadiri University, 2022)
In construction management, project scheduling is an important thing to note. The project schedule is a means of determining proper duration, controlling implementation progress, and allocating resources efficiently. Improper scheduling will have an impact on project delays. the project for the construction of a double track railway across the south of Java between Mojokerto-Sepanjang is planned to be completed in 60 weeks with overlapping activities due to changes in activities. This double track rail project is an ongoing project. This research aims to find out the project implementation time using the Line of Balance. The development project has a length of 3011.23 m. the Line of Balance method is carried out by determining the dependency logic, preparing a Line Of Balance schedule, drawing a Line Of Balance graph, and determining the production speed. The results of the study show that the line of balance schedule in the existing conditions has lines of intersection between jobs. The intersection indicates that there is overlapping work. For this reason, improvements are made by changing the dependency logic from work that was originally parallel to not parallel. The results of improvements made by reducing the duration per work cycle by 1 week revealed that the duration of the project could be accelerated to 38 weeks. So that the scheduling can be used to speed up the time of implementation of project activities.